Carry forth the stories : an ethnographer's journey into native oral tradition - Frey, Rodney, 1950- (Washington State University Press, 2017)
Seasoned anthropologist/ethnographer Rodney Frey offers personal and professional insights into the power and value of storytelling gleaned from more than forty years of working successfully with indigenous peoples. He frames his "ethnographic memoir" as "the quest of an ethnographer to learn from his hosts and engage in collaborative, applied, ethical-based research, writing, and classroom pedagogy." He addresses cultural property rights, tribal review, and giving back to host communities, along with indigenous learning styles, perspectives, and knowledge. His collaborative research projects with the Crow, Coeur d'Alene, Nez Perce, and Warm Springs tribes offer a model for others seeking to work with Native communities. In Carry Forth the Stories, Frey intertwines stories gathered from interviews, oral histories, and elders. He also shares facets of his own cancer journey seeking therapy from both Native and Western healing traditions.